2021
DOI: 10.1002/ehf2.13498
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of rehabilitation in chronic heart failure: evaluating the reporting of exercise interventions

Abstract: A large body of research supports the use of exercise to improve symptoms, quality of life, and physical function in patients with chronic heart failure. Previous reviews have focused on reporting outcomes of exercise interventions such as cardiorespiratory fitness. However, none have critically examined exercise prescription. The aim of this review was to evaluate the reporting and application of exercise principles in randomised control trials of exercise training in patients with chronic heart failure. A sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 174 publications
0
7
0
Order By: Relevance
“…It plays a powerful role in preventing SCD caused by malignant arrhythmias. Mortality can be reduced through appropriate testing and subsequent measures, and life-threatening ventricular arrhythmias can be treated [ 17 ]. However, during the treatment of ICD/CRT-D defibrillation, some patients may have incorrect discharge for nonventricular tachycardia (VT)/ventricular fibrillation (VF).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays a powerful role in preventing SCD caused by malignant arrhythmias. Mortality can be reduced through appropriate testing and subsequent measures, and life-threatening ventricular arrhythmias can be treated [ 17 ]. However, during the treatment of ICD/CRT-D defibrillation, some patients may have incorrect discharge for nonventricular tachycardia (VT)/ventricular fibrillation (VF).…”
Section: Discussionmentioning
confidence: 99%
“…The inappropriate discharge is one of the most serious adverse events after ICD/CRT-D implantation. These patients who receive inappropriate discharge may lead to physical pain, emotional anxiety, and impaired quality of life, even malignant arrhythmias [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure is one of the top leading causes of death worldwide. Exercise is the best intervention for prevention and even treatment of heart failure without causing further cardiac injuries [ 59 , 60 , 61 , 62 , 63 ]. An early study in exercise intervention in human chronic heart failure patients in 1999 showed that one year of moderate intensity cycling (60% VO 2 max) led to better cardiac outcomes and quality of life improvements [ 64 ].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…[5] A large body of research supports the use of exercise, such as high-intensity interval training, medium-intensity training, and resistance training, which can improve symptoms, quality of life, and physical function in patients with CHF. [5] YB and BH contributed equally to this work. This study was supported by Combined Chinese and Western medicine for the treatment of chronic heart failure with preserved ejection fraction (ZXYXZ-201903).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mortality rate is still high [4] . Regardless of the etiology, CHF can benefit from exercise-based cardiac rehabilitation (CR) [5] . A large body of research supports the use of exercise, such as high-intensity interval training, medium-intensity training, and resistance training, which can improve symptoms, quality of life, and physical function in patients with CHF [5] …”
Section: Introductionmentioning
confidence: 99%